2018
DOI: 10.1111/jpm.12470
|View full text |Cite
|
Sign up to set email alerts
|

The perspectives of former recipients and experts on stigmatization related to electroconvulsive therapy in Denmark: A focus group study

Abstract: WHAT IS KNOWN ON THE SUBJECT?: Electroconvulsive therapy (ECT) has existed worldwide for nearly 80 years. ECT is a fast-working and potentially life-saving treatment, but it is considered controversial. Although frequently mentioned, stigmatization in relation to ECT has not been systematically explored so far. WHAT THIS PAPER ADDS TO EXISTING KNOWLEDGE?: This paper provides new insight into both recipient and expert perspectives on ECT. It identifies several issues of stigmatization related to ECT and suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Study participants also highlighted a lack of sufficient information provision in and outside the clinical setting. This is concerning, considering that participants have reported the clinic as their main source of information, and scarce or biased information as coming from other sources or society [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study participants also highlighted a lack of sufficient information provision in and outside the clinical setting. This is concerning, considering that participants have reported the clinic as their main source of information, and scarce or biased information as coming from other sources or society [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stigmatizing attitudes and behaviors concerning ECT are closely related to one‘s personal and factual knowledge ( Kring et al, 2018 ). Accurate information and learning by participating in EKTs were proven to increase knowledge and improve attitudes toward ECT significantly in physicians, nurses, patients, and relatives ( Aoki et al, 2016 ; Li et al, 2016 ; Alexander et al, 2020a , b ).…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, ECT has proved more tolerable than classical antidepressants when taking side effects into consideration (Payne & Prudic, 2009), and many positive patient accounts of ECT exist (Knight et al., 2017; Maguire et al., 2016 ) . Despite this, ECT remains one of the most controversial and potentially misunderstood treatments available (Kring et al., 2018; Maguire et al., 2016). A lot of this controversy rests in the unresolved questions relating to the mechanisms of ECT and the associated side effects (Donahue, 2000; Sackeim, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A lot of this controversy rests in the unresolved questions relating to the mechanisms of ECT and the associated side effects (Donahue, 2000; Sackeim, 2014). The early history of coercion and unmodified practices do nothing to quell the mistrust that surrounds the procedure (Kring et al., 2018). In one qualitative study exploring the decision‐making towards ECT in older adults, stigma was identified as a major hurdle in electing to ECT (Amazon et al., 2008).…”
Section: Introductionmentioning
confidence: 99%